Classical Guidance With a Problem Based Learning Approach to Improve High Shool Students Understanding of Sex Grooming - M. Fatchurrahman; Rafli Gustommy Pratama; Asep Solikin; Suniati Suniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Sexual grooming is a form of non-physical abuse that can occur in subtle and manipulative ways, and is often unrecognised by the victims, particularly schoolchildren who lack the understanding and experience to recognise and understand these covert forms of abuse. This study aims to determine the effect of classical guidance using a Problem-Based Learning (PBL) approach on improving high school students' understanding of sex grooming. The study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research subjects were 11th-grade students at Muhammadiyah High School in Palangka Raya, selected using simple random sampling. The research instrument was a sex grooming understanding scale that had undergone validity and reliability testing. Data analysis techniques used the Wilcoxon Signed Ranks Test nonparametric statistical test. Based on the results of the Wilcoxon analysis, the Asymp. Sig. (2-tailed) value is 0.238, which is greater than the significance level of 0.05. Based on these results, it can be concluded that there is no statistically significant difference between the pretest and posttest scores. Thus, the null hypothesis (H0) is accepted, while the alternative hypothesis (Ha) cannot be accepted. These findings indicate that classical guidance services with a problem-based learning approach have not shown statistically significant changes in understanding in the context and conditions of this study. However, descriptively, there is a tendency for changes in scores in some students, which indicates a learning process and internalization of material during the service.